Анализ двигательных реакций позвоночных животных - Солуха, Б.В. (Вестник зоологии, 1979)
Motor reactions of animals are considered as realization of a nonstationary random process, which permits elaborating the method of measuring characteristics for detection of the reactions and the stimulus-reaction dependences. An example of an empiric formula for this dependence is given for the yellow-spotted fire-bellied toad reactions to distant stimulation by the electric field. Its relation to the stimulus-sensation empiric formula is discussed. An experimental stand is described for measuring motor reactions in the vertebrates.